Habituation of Religious Literacy as an Effort to Cultivate Moderation Values towards Students at SMK Negeri 7 Bandar Lampung - Juliantika Juliantika; Sa'idy Sa'idy; Muhammad Mustofa; Umi Hijriyah (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2024)
Education makes intelligent individuals independent in their environment. Therefore, it is interesting to study the efforts of Islamic Religious Education teachers in familiarizing religious literacy that contains moderation values. The purpose of this study is to analyze the various efforts made by Islamic Religious Education teachers in instilling religious moderation values in students at SMK Negeri 7 Bandar Lampung. the method that researchers use is the qualitative method. The data collection techniques used are observation, interview, and documentation. The results of this study reveal that PAI teachers at SMK Negeri 7 Bandar Lampung have implemented religious literacy habituation through the stages of Qudwah, Uswah, Ta'lim, and Ta'wid. There are inhibiting factors and supporting factors in the habituation of religious literacy, both internal factors such as student personality, as well as external factors from family and peers.